Fatigability of trunk muscles when simulating pushing movement during treadmill walking - Peng, Y.; Lin, Y.; Lien, H. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Pushing is a common movement in moving objects, and it also related to about 9% to 20% low back injuries occurrence (Hoozemans et al., 1998). The purpose of the present study was to examine the effect of fatigue on trunk muscle activity during treadmill walking with and without a pushing movement.